Immunogenicity of the BNT162b2 mRNA Covid-19 vaccine in elderly people over 85 years of age in Greece: the GREVAXIMO study - Kontopoulou, Konstantina; Nakas, Christos Theodore; Ainatzoglou, Alexandra; Ifantidou, Athina; Ntotsi, Paschalina; Katsioulis, Christos; Papazisis, Georgios (Aging clinical and experimental research, 2021)
Background Elderly people aged over 85 years were among the first groups to receive the BNT162b2 mRNA Covid-19 vaccine in Greece according to the national priority assignment policy. Aim The aim of this study was to provide useful insight into the antibody generation taking place post-immunization in elderly individuals aged over 85. Methods In the first phase of our study, antibody levels were monitored in a total of 400 participants, while our final sample consisted of 297 subjects. Humoral immune responses were recorded in 69.75% (95% CI 65.25–74.25) of vaccinees post-first dose and in 98.99% (95% CI 97.85–100) post-second dose. Results Overall, a remarkable 40-fold change in IgG levels was observed between the two doses. Subjects displaying low antibody levels after the first dose had significantly higher IgG fold changes than vaccinees whose initial antibody levels were high. Conclusion Taken together, our findings highlighted the high fold change (41.18) recorded in the titers of neutralizing antibodies after the second dose suggesting the need for its timely administration to elderly individuals.